'I don’t fit this intercultural profile. I am kind of different.' a Critical Reflection on the Possible Effect of Cultural Attribution Bias in Intercultural Competence Assessment Materials Design - Muszyńska, Barbara; Ditze, Stephan-Alexander (INSTED: Interdisciplinary Studies in Education & Society, 2024)
This article aims to report data from the implementation of intercultural competence assessment activities conducted in a secondary school in Germany. The study involved qualitative content analysis and critical reflection as a method of inquiry. The findings show that the design of the intercultural profile task in the Assessor Manual used in the study reflects Cultural Attribution Bias (CAB) which may contribute to false end results when working with young people from diverse backgrounds.. Such materials may implicitly and unwittingly support bias and, what is more, socialize learners into accepting it. Bearing that in mind, the teachers’ ability to think and reflect critically on the effectiveness of different assessment activities and tools used with students is crucial in organizing the education process and for the well-being of the students.